"iM Ready to Learn": Undergraduate Nursing Students Knowledge, Preferences, and Practice of Mobile Technology and Social Media. Issue 1 (January 2017) - Hay, Benjamin; Carr, Peter J.; Dawe, Lydia; Clark-Burg, Karen
Abstract : The purpose of this study was to identify in what way social media and mobile technology assist with learning and education of the undergraduate nurse. The study involved undergraduate nursing students across three campuses from the University of Notre Dame Australia. Participants were invited to complete an online questionnaire that related to their current knowledge, preferences, and practice with mobile technology and social media within their undergraduate nursing degree. A quantitative descriptive survey design was adapted from an initial pilot survey by the authors. A total of 386 nursing students (23.47% of the total enrolment) completed the online survey. Overall, results suggested that students are more supportive of social media and mobile technology in principle than in practice. Students who frequently use mobile technologies prefer to print out, highlight, and annotate the lecture material. Findings suggest that nursing students currently use mobile technology and social media and are keen to engage in ongoing learning and collaboration using these resources. Therefore, nursing academia should encourage the appropriate use of mobile technology and social media within the undergraduate curriculum so that responsible use of such technologies positively affects the future nursing workforce.